2014
DOI: 10.3389/fpsyg.2014.01471
|View full text |Cite
|
Sign up to set email alerts
|

Another step closer to measuring the ghosts in the nursery: preliminary validation of the Trauma Reflective Functioning Scale

Abstract: The aim of this study was to examine preliminary evidence of the validity of the Trauma Reflective Functioning Scale and to investigate reflective functioning (RF) and attachment in pregnant women with histories of trauma, with a particular focus on the capacity to mentalize regarding trauma and its implications for adaptation to pregnancy and couple functioning. The Adult Attachment Interview was used to assess attachment, unresolved trauma and mentalization (measured as RF) regarding relationships with attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 61 publications
8
83
2
7
Order By: Relevance
“…From a theoretical perspective, certain types of play facilitating the imagination of the roles and perspective of others may be more likely to facilitate the development of mentalization. At the same time, mentalization regarding self can be expected to be more closely related to the mother's (or primary caregiver's) interest in the subjectivity of the child, as reflected in previous findings that maternal RF predicts children's RF regarding themselves (Ensink et al, 2014).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…From a theoretical perspective, certain types of play facilitating the imagination of the roles and perspective of others may be more likely to facilitate the development of mentalization. At the same time, mentalization regarding self can be expected to be more closely related to the mother's (or primary caregiver's) interest in the subjectivity of the child, as reflected in previous findings that maternal RF predicts children's RF regarding themselves (Ensink et al, 2014).…”
Section: Discussionmentioning
confidence: 82%
“…Play, reflective functioning, and sexual abuse Mentalization is a potential resilience factor in the context of abuse Ensink, Berthelot, Bernazzani, Normandin, & Fonagy, 2014;Fonagy, Steele, Steele, Higgitt & Target, 1994); however, sexual abuse has a negative impact on mentalization and RF in children . Play is also affected in the context of traumatic experience (Alessandri, 1991;Cunningham, Fill, & Al-Jamie, 1999;Fonagy & Target, 2000).…”
Section: Mentalization and Reflective Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it became crucial to empirically investigate parental reflective functioning in mothers who were abused in their childhood. Ensink et al (2014) hypothesized that it is specifically the ability to mentalize one’s own past traumatic experiences rather than the mother’s general mentalizing capacity that prevents her from inadequate caregiving. In a sample of 100 pregnant women who had suffered from childhood abuse and neglect, they found that reflective functioning about the traumatic experiences was lower than the general mentalization about their childhood, and that low mentalization about the traumatic experiences was the best predictor of the difficulty to invest in the pregnancy as well as of the lack of positive expectations about becoming a mother.…”
Section: Resultsmentioning
confidence: 99%
“…The capacity to envision mental states in others grows out of a process of self-understanding, which in turn depends on the other's capacity to perceive the self as thinking and feeling (Sharp and Fonagy 2008). A secure caregiver-child relationship would be expected to facilitate this virtuous cycle, particularly as the security of the relationship is enhanced by the caregiver's capacity to mentalize the child (Berthelot et al 2015;Ensink et al 2014;Fonagy and Target 2005). Thus, to the extent that truth and mentalizing are linked in the experience of mutual understanding, secure attachment could almost be seen as coterminous with the experience of truth, or at least as a key route toward this experience.…”
Section: Personal Truth and Epistemic Trustmentioning
confidence: 99%